Hubungan Antara Pola Asuh Orangtua dengan Minat Belajar Siswa Kelas Tinggi Sekolah Dasar - St Jauhar; awaluddin muin; latri aras; rosna sari hikma (Universtas Negeri Makassar, 2022)
The problem in this research is the lack of parenting styles where parents are the first mandate for their children in various aspects of life. This research is a quantitative research with a correlational type of research which aims to determine the relationship between parenting patterns and the learning interest of high-class students at SDN 26 Watang Palakka. The results showed that there was a significant relationship between parenting patterns and the learning interest of high-class students at SDN 26 Watang Palakka with a value of Xnitung (17.035) > X value (9.48773) which means H, rejected and H, accepted. Based on the data analysis, it can be concluded that the parenting applied by parents to students will have an impact on students' mindsets in learning so that it will affect students' motivation and interest in learning. And the conclusion, the impact of this research is that the application of good parenting for students will increase student interest in learning.